Work-family demands, resources and outcomes among Filipino call center agents - Puthukulangara, Abraham (Animo Repository, 2010)
This study explored the work-family demands, resources and derived outcomes of selected young Filipino call center agents in Metro Manila. The participants of the study consisted of 12 adults (five females and seven males) within the age bracket of 21-34 years. Utilizing the qualitative research design, in-depth interviews were employed for data collection. Data was analyzed using Consensual Qualitative Research Method (CQR). This research adopted Hill’s ecological systems theory as the framework of the study. Overall, results revealed that work-family-personal demands (call center work characteristics and its pressure, family demands and its strain, and intrapersonal demands consisted of health concerns, fears and anxieties of agents) and work-family-personal resources (work resources consisted of good compensation, ambiance, incentives and positive commendations, social support, family support and, personal attributes like positive outlook, empathy, friendliness and other coping strategies like relaxation, healthy and disciplined life)interact with each other and bring about positive and negative effects on their outcome. The findings of the study indicated that the Filipino cultural, familial and interpersonal values have a bearing on the call center agents’ experiences. In the process of their experience as call center agents they are challenged by the demands of work, family, social and intrapersonal factors. However, their survival is mostly depending on the availability of different resources they get from work and family. The study also discussed the result of healthy interaction between the demands and resources, unhealthy outcomes, perceived meaning given to the demands and resources and their coping strategies. Based on the findings, certain conclusions and recommendations are made to help the Filipino call center agents.